One-Pot Synthesis of β-Keto Esters and Preparation of 3-Ketopalmitoyl-CoA - Košak, Urban; Kovač, Andreja; Gobec, Stanislav (Synlett, 2012)
β-Keto esters were synthesized from acyl chlorides and sodium ethyl acetoacetate in EtOH using a simple ‘one-pot, one-step’ method. The deacetylation of α-acetyl β-keto ester to β-keto ester was performed simply, by heating the reaction mixture at reflux for 12 hours, without the addition of additional reagents (e.g., NH4Cl, NH3, MeOH, or NaOH). One of the β-keto esters prepared using this method was ethyl 3-oxohexadecanoate, a key intermediate in the synthesis of 3-ketopalmitoyl coenzyme A (3-oxohexadecanoyl coenzyme A), a potential substrate of the biologically important enzyme 17β-hydroxysteroid dehydrogenase type 12.
Keywords: β-keto esters; one-pot reaction; deacetylation; 3-ketopalmitoyl coenzyme A; 17β-hydroxysteroid dehydrogenase type 12